Evaluation of the oscillometric technique for intermittent non-invasive arterial blood pressure measurement in the anaesthetized pig. (April 2013) - Ypsilantis, P; Didilis, V; Simopoulos, C
This study was designed to evaluate the oscillometric technique for intermittent non-invasive measurement of arterial pressure (AP) in the anaesthetized pig. In six pigs under sevoflurane anaesthesia, intermittent (every 2 minutes) oscillometric measurements of AP made at a forelimb (FL), a hindlimb (HL) and the tail base were compared with simultaneous direct AP measurements made at the aortic arch (AA) over a wide pressure range (30–140 mmHg of mean AP). All oscillometric measurements strongly correlated (Pearson correlation coefficient >0.837, P < 0.001) with direct AP measurements, with those made at the FL exhibiting the highest correlation. On the basis of consistency of difference between oscillometric and AA pressure readings at graded pressure levels, measurements made at the tail base provided reliable prediction of systolic AP, at the FL of diastolic AP and at both the tail base and the FL of mean AP. In conclusion, oscillometric measurements at the FL and the tail base offer reliable prediction of AP in the anaesthetized pig.